Histamine: a new immunomodulatory player in the neuron-glia crosstalk - Rocha, Sandra M.; Pires, Joel; Esteves, Marta; Graça, Baltazar; Bernardino, Liliana (Frontiers in Cellular Neuroscience, 2014)
Histamine is an amine acting as a major peripheral inflammatory mediator. In the brain, histamine was initially viewed as a neurotransmitter, but new evidences support its involvement in the modulation of innate immune responses. Recently, we showed that histamine modulates microglial migration and cytokine release. Its pleiotropic actions, ranging from neurotransmission to inflammation, highlight histamine as a key player in a vast array of brain physiologic activities and also in the pathogenesis of several neurodegenerative diseases. Herein, we emphasize the role of histamine as a modulator of brain immune reactions, either by acting on invading peripheral immune cells and/or on resident microglial cells. We also unveil the putative involvement of histamine in the microglial-neuronal communication. We first show that histamine modulates the release of inflammatory mediators, namely nitric oxide, by microglia cells. Consequently, the microglia secretome released upon histamine stimulation fosters dopaminergic neuronal death. These data may reveal important new pharmacological applications on the use histamine and antihistamines, particularly in the context of Parkinson’s disease.